Increasing Purchasing Decisions Through Creating Purchase Interest on Xiaomi Consumers in Semarang - Ardien, Moh Arif Iskandar; Nurhayati, Nurhayati; Firdaus, Firdaus; Febriana, Shalma (Economics and Business International Conference Proceeding, 2024)
Technological developments are growing every day, this can be seen from the emergence of more and more cellphone brands on the market, but this makes consumers increasingly confused about their choices. This research aims to describe the role of Brand Ambassadors in increasing purchasing decisions through consumer purchasing interest. The population of this research was Xiaomi consumers in the city of Semarang and in determining respondents used purposive sampling with criteria, so that the number of respondents selected was 100. The data collection technique used a 1-5 scale questionnaire and was processed using smart PLS. The results of this research suggest that Brand Ambassadors can influence the decision to purchase Xiaomi products both directly and through purchase interest. To survive in the world of technology business, hard work and smart (innovation) are needed to attract consumers' attention, and in this research, consumers also turned out to be very selective in choosing the cellphone products consumers need.